Penggunaan buku cerita bergambar elektronik interaktif di sekolah dasar (studi kasus di kelas 2 SD N Bangka 05 Jakarta Selatan) - Gemala Qurbani; Siti Nafingah (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2022)
Technology is growing very fast, including on medium that used to study in primary school. Reading lesson have many strategic to used, one of them is using an interactive electronic picture book. Present research revealed how interactive electronic picture book used in grade 2 SDN Bangka 05, Jakarta Selatan. Book created by the teacher used in this lesson, combine the image, text, and voice in order to more interactive and gain the student interest. Before the lesson start, teacher diagnosed student reading skill using printed book, and the result show that student read the book with a flat voice, there is no intonation while the reading. Narrative qualitative method used in this research. The result show there is increasing enthusiastic among student compared when using printed book. Beside that there is an increasing on reading comprehensive too and student can show their understanding about story through role playing in the class. Further research needed to conduct in other school with variety resources.